Cross-cultural adaptation of the Cyberchondria Severity Scale for Brazilian Portuguese - Silva,Fernanda Gonçalves da (2016)
Abstract Introduction: The internet has proven to be a valuable resource for self-care, allowing access to information and promoting interaction between professionals, caregivers, users of health care services and people interested in health information. However, recurring searches are often related to excessive health anxiety and a phenomenon known as cyberchondria can have impacts on physical and mental health. Within this background, a Cyberchondria Severity Scale has been developed to differentiate healthy and unhealthy behavior in internet searches for health information, based on the following criteria: compulsion, distress, excesses, and trust and distrust of health professionals. Objective: To conduct cross-cultural adaptation of the Cyberchondria Severity Scale for Brazilian Portuguese, because of the lack of an appropriate instrument for Brazil. Methods: This study was authorized by the original author of the scale. The process was divided into the following four steps: 1) initial translation, 2) back-translation, 3) development of a synthesized version, and 4) experimental application. Results: Translation into Brazilian Portuguese required some idiomatic expressions to be adapted. In some cases, words were not literally translated from English into Portuguese. Only items 7, 8, 12, 23 and 27 were altered, as a means of both conforming to proper grammar conventions and achieving easy comprehension. The items were rewritten without loss of the original content. Conclusion: This paper presents a translated version of the Cyberchondria Severity Scale that has been semantically adapted for the Brazilian population, providing a basis for future studies in this area, which should in turn contribute to improved understanding of the cyberchondria phenomenon in this population.